Alum-based Herbal Handwash: Formulation and Evaluation Study - Umarkar, Mohit J.; Jibhkate, Pawan V.; Thakare, Payal G.; Banarase, Nilesh B.; Gabhane, Koshish B.; Salode, Vikrant L. (Indian Journal of Pharmacy & Drug Studies, 2024)
Hand washing is one of the most important strategies for preventing the spread of surface-borne diseases. A variety of hand washes are currently available on the market, the majority of which are alcohol-based and synthetic. Since synthetic substances can cause various allergic reactions among people, as well as roughness of the skin, society's interest has shifted towards the use of herbal hand washes. However, in addition to the herbal extracts, we investigated alum as one of the most ancient and effective antimicrobial ingredients in hand wash formulations. In this study, F-1 to F-5 formulation batches of hand washes were prepared using a trial and error method by varying the quantity of ingredients used. In these formulations, hydro-alcoholic extracts of lemon peels and reetha, as well as lemon grass oil as a volatile oil and alum as a mineral, were used as the main constituents, which were analysed by phytochemical screening. These formulations were then evaluated using a variety of methods, such as pH, foam height, foam retention, skin irritation, stability study, and an antimicrobial assay. According to our findings, the alum-based F-3 formulation performed significantly better than the other formulations. With the success of this study, we can conclude that, in the future, as herbal drug technology advances, various hygienic and life-saving products will firmly hold their place in human life.